F = t ⇨ df = dt
dg = sec² 2t dt ⇨ g = (1/2) tan 2t
⇔
integral of t sec² 2t dt = (1/2) t tan 2t - (1/2) integral of tan 2t dt
u = 2t ⇨ du = 2 dt
As integral of tan u = - ln (cos (u)), you get :
integral of t sec² 2t dt = (1/4) ln (cos (u)) + (1/2) t tan 2t + constant
integral of t sec² 2t dt = (1/2) t tan 2t + (1/4) ln (cos (2t)) + constant
integral of t sec² 2t dt = (1/4) (2t tan 2t + ln (cos (2t))) + constant ⇦ answer
Answer:
<h2>x³ + x² - 3x - 3</h2>
Step-by-step explanation:
I'm assuming g*f means g times f, so you want to multiply the two functions together.
(x² - 3)(x + 1) Since the product is 2 binomials, use FOIL
= x²(x) + x²(1) - 3(x) - 3(1)
which simplifies to
<h2>x³ + x² - 3x - 3</h2>
X^2-4x-5=0
according viet’s theorem
the roots are 5 and -1
Answer: -10 ÷ -2/5
Step-by-step explanation: this would equal 25 which is greater than 10. Hope this helps!